2017
DOI: 10.5194/acp-17-13983-2017
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation of GNSS zenith total delays from a Nordic processing centre

Abstract: Abstract. Atmospheric moisture-related information estimated from Global Navigation Satellite System (GNSS) ground-based receiver stations by the Nordic GNSS Analysis Centre (NGAA) have been used within a state-of-the-art kilometre-scale numerical weather prediction system. Different processing techniques have been implemented to derive the moisture-related GNSS information in the form of zenith total delays (ZTDs) and these are described and compared. In addition full-scale data assimilation and modelling exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Authors also identify no clear benefit of 4DVAR against 3DVAR. (Lindskog et al, 2017) in their Nordic country study of GNSS ZTD impact on forecasts, confirmed that the forecasts are sensitive to thinning distance. Shorter distance between stations (below 100km) leads to a 25 larger humidity bias in the lower troposphere, which may explain the humidity bias in the (Bennitt and Jupp, 2012) solution.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Authors also identify no clear benefit of 4DVAR against 3DVAR. (Lindskog et al, 2017) in their Nordic country study of GNSS ZTD impact on forecasts, confirmed that the forecasts are sensitive to thinning distance. Shorter distance between stations (below 100km) leads to a 25 larger humidity bias in the lower troposphere, which may explain the humidity bias in the (Bennitt and Jupp, 2012) solution.…”
Section: Introductionmentioning
confidence: 79%
“…Shorter distance between stations (below 100km) leads to a 25 larger humidity bias in the lower troposphere, which may explain the humidity bias in the (Bennitt and Jupp, 2012) solution. (Lindskog et al, 2017) showed that the humidity forecast is better when the GNSS ZTD is assimilated with other meteorological observations such as Advanced Microwave Sounding Unit (AMSU) or Infrared Atmospheric Sounding Interferometer (IASI) radiances. Authors also showed that the adopted bias correction strategy and GNSS ZTD estimation procedure have marginal impact on the forecasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this diagnostic purpose, a revised whitelist is generated with zero thinning in order to execute very first active assimilation and to collect its OMF departures. Liu and Rabier (2003) showed that horizontal thinning distance is optimal, where the observation error correlations are less than 0.2-0.3. By the visualisation of these error correlations, which can be seen in Fig.…”
Section: Results Of the Preselection Proceduresmentioning
confidence: 99%
“…In addition, extended parallel experiments will be carried out in a preoperational context. These runs should also include various types of quality control, like a background check [40] and rejection in particular areas [39].…”
Section: Discussionmentioning
confidence: 99%